PENGARUH KELENGKAPAN PERALATAN WORKSHOP PEMBUATAN ALAT PERAGA MATEMATIKA TERHADAP HASIL BELAJAR MAHASISWA - Dwi Sulistyaningsih; Venissa Dian Mawarsari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The aim of this study is to determine the effect of the availability of practical equipment on student learning outcomes in department of mathematics education di University Muhammadiyah Semarang. The populations are lecturers and students who are in the fourth semester in that department. While the sample are 23 students  who took the course of workshop mathematical equipment. Data were collected through observation, questionnaires and documentation. Analysis of influence test by using linear regression test. The result showed that the average of students' learning achievement is 77.3. While the effect of the availability of practice equipment to students' learning achievement is 23,4%. Keywords: workshop, mathematics manipulative, learning proses